Performance optimisation of control channel in ForCES‐based software defined network. Issue 6 (1st November 2016) - Li, Chuanhuang; Gong, Liang; Cen, Lijie; Wang, Weiming
Abstract : The traditional network architecture cannot meet the growing needs of increasingly diverse network applications. The new generation network architectures, software defined network (SDN) which have features of high openness, flexibility, scalability and high controllability have widely been studied. However, a series of new problems are also produced in this new architecture, such as security problem resulted from the high openness, and performance problem resulted from the high flexibility. Currently, the researchers are mainly concentrated in the implementation and standardisation of SDN. There is no good approach to evaluate and optimise the system performance. This studies the performance problems unresolved in SDN research area, and proposed an idea and method to analyse the control channel of ForCES (Forwarding and Control Element Separation)‐based SDN by using the stochastic network calculus theory. First, the architecture of ForCES‐based SDN is introduced. Then, the performance model of the channel is given. Based on the model, an optimisation method to performance is detailed. This study also gives a simulation by using NS‐2 (Network Simulator, Version 2) to verify the correctness and reliability of the performance model.